Public-Private Environment in the Port Operation Decision-Making Process in Brazil: a case study - Serra, Laura Thomaz e; Martins, Ricardo Silveira; Bronzo, Marcelo (Review of Business Management, 2009)
Regarding the decisions of microeconomic and managerial nature, the increasing acknowledgment of the importance of the transport decisions for the logistics performance is noticed, once the transport decisions assume relevant trade-offs with other logistics functions and processes, such as inventory, warehousing, purchasing as well as directly affects the outcomes of the logistics services and costs. This implies in considering the transport mot as a “derived demand” in the neoclassic tradition, but as explicative variables of the management decisions. Therefore, the present study seeks to evaluate the public-private relationship in the process of decision making in companies, with the objective of analyzing the export process under the perspective of the decisions oriented to the transaction costs management in the company. In short, the research points out that the public-private relationship shows as a result inappropriate environment, tightening the competition on the global scenario. In the case studied the basic parameters around which the attributes are formed, cost and level of service are adversely affected by this relationship. In turn, the institutional environment in Brazil, with regard to port operations, imposes severe transaction costs. Key words: Transport. Public-private environment. Port operation. Logistics. Exportation. Decision making. Trade-offs.